The Nexus between Technological Advancement and CO2 Emissions in Malaysia - Yuaningsih, Lilis; Febrianti, R. Adjeng Mariana (International Journal of Energy Economics and Policy, 2021)
The key obstacles to attaining the prevailing goal of viable development are environmental degradation and climate change. Copious efforts have been made in this field, but still, the policy embraced and the empirical connection among the factors of carbon dioxide emissions are not evident. The connection between the variables of the analysis is subject to a theoretical and statistical inconsistency in the research. Through this research work, the association between carbon dioxide emissions and its determinants such as economic growth, energy use, financial development and technical progress is examined in Malaysia for the period from 1985 to 2019. The auto-regressive distributed lag method is employed to estimate long-run parameters. The results indicate that during the research period TI has an inverse but negligible impact on pollution in Malaysia. The analysis further shows that higher growth of economy increases long-term environmental efficiency and is consistent with the Kuznets environmental hypothesis. Also, the findings show that financial sector development would minimize emissions of carbon dioxide, thereby enhancing environmental quality in Malaysia. The short-term findings do not validate the EKC hypothesis. The Granger causality results reveal a two-way causality ranging from the growth of the economy to carbon dioxide emissions and TI to carbon dioxide emissions. Keywords: CO2 emissions, Technological Growth, GDP, Malaysia JEL Classifications: O3, Q3 DOI: https://doi.org/10.32479/ijeep.11888